2008
DOI: 10.1590/s1807-59322008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Malnutrition and Inflammatory Response in Critically Ill Children and Adolescents Admitted to a Tertiary Intensive Care Unit

Abstract: Delgado AF, Okay TS, Leone C, Nichols B, Del-Negro GM, Costa-Vaz FA. Hospital malnutrition and inflammatory response in critically ill children and adolescents admitted to a tertiary intensive care unit. Clinics. 2008;63:357-62.Critical illness has a major impact on the nutritional status of both children and adults. A retrospective study was conducted to evaluate the incidence of hospital malnutrition at a pediatric tertiary intensive care unit (PICU). Serum concentrations of IL-6 in subgroups of well-nourish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
1
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 25 publications
(43 reference statements)
3
63
1
16
Order By: Relevance
“…Hospital undernutrition is a known risk factor for morbidity and mortality in children, adolescents, and adults (1,2). Malnutrition has been shown to affect patient outcome and represents a continuous spectrum ranging from marginal nutrient status to severe metabolic and functional alterations, with different degrees of relative alterations of body weight and body composition (3).…”
Section: Introductionmentioning
confidence: 99%
“…Hospital undernutrition is a known risk factor for morbidity and mortality in children, adolescents, and adults (1,2). Malnutrition has been shown to affect patient outcome and represents a continuous spectrum ranging from marginal nutrient status to severe metabolic and functional alterations, with different degrees of relative alterations of body weight and body composition (3).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that malnutrition does not affect CRP production in response to infections. 33,34 In a study in Malawi, although children with kwashiorkor had reduced rates of protein breakdown and synthesis, their CRP levels were similar to those without kwashiorkor. 35 To our knowledge, only 1 study found that CRP levels in response to infection are lower in malnourished than in wellnourished children.…”
Section: Discussionmentioning
confidence: 99%
“…These patient populations are known to be most vulnerable to postoperative morbidity, and are most vulnerable to further nutritional depletion during their inpatient stay. 6,9,10 There is a need for large, adequately powered prospective studies incorporating a gold-standard method for nutritional assessment, with robust and consistently applied definitions of undernutrition and infectious complications. If undernutrition is a risk factor for infection, aspects of pre-and postoperative feeding practices could be modified in order to reduce the physical, psychosocial and financial burdens associated with HCAIs in children.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is evidence that nutritional status deteriorates in children following hospital admission, 6,7 often when associated with chronic or critical illness. 8,9 Poor nutritional status (measured by lower weight-for-age zscores) has been associated with increased duration of mechanical ventilatory support, increased length of stay and increased one-year mortality in neonates undergoing surgery within an intensive care setting. 10 A recent evidence-based review of the literature found weak evidence of preoperative nutritional assessment being predictive of adverse clinical outcomes in paediatric surgical patients.…”
Section: Introductionmentioning
confidence: 99%